J.M. Coetzee and the Politics of Style. - Zimbler, Jarad (Cambridge University Press, 2014)
This is the first book-length study of the distinctive style of J.M. Coetzee's early and middle fictions.
Includes index.
Keywords: Coetzee, J. M., -- 1940- -- Criticism and interpretation.; Coetzee, J. M., -- 1940-; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Criticism, interpretation, etc.